IMPLEMENTATION OF SOCIAL EMOTIONAL LEARNING THROUGH THE GP (GALON PERUNDUNGAN) AND AKU PEKA (PEDULI, EMPATI, KASIH SAYANG) PROGRAM AT SENDANGMULYO 02 STATE PRIMARY SCHOOL - Azizah; Sumarno; Yenny Rachmawati (STKIP Subang, 2024)
Bullying is something you need to be careful of because it not only damages you physically but also mentally. Even more dangerous, victims of bullying can commit suicide because they do not have the resilience to face this behavior. Bullying can occur due to environmental factors, both physical internal environment and cultural and technological aspects. The ease with which a person can access the internet and the development of online game applications today is one of the causes of a person's moral degradation. Bullying can occur anytime and anywhere, including in the world of education. Schools are an environment where bullying against children develops. The efforts made by SDN Sendangmulyo 02 to prevent bullying in schools are by implementing social emotional learning for students which is framed in a special program called